2019
DOI: 10.1186/s43141-019-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a cucumber alanine aminotransferase2 gene improves nitrogen use efficiency in transgenic rice

Abstract: BackgroundRice can absorb less than 40% of applied nitrogen fertilizer, whereas the unabsorbed nitrogen fertilizer may cause environmental problems, such as algal blooms in freshwater and increased production of nitrous oxide, a greenhouse gas which is 300 times more potent than carbon dioxide. Development of nitrogen use efficient (NUE) rice is essential for more environmentally friendly rice production. Recently, NUE rice has been developed by root-specific expression of alanine aminotransferase (AlaAT) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Meanwhile, the M50 line revealed the highest shoot biomass and grain contents at a nitrogen fertilizer dose of 120 kg ha-1 (N3) (Figure 4). These results were in accordance with Sisharmini et al (2019) reported an increase in grain yield and tiller numbers was observed in transgenic events at 90 kg ha -1 N. 2007) and (Shrawat et al 2008) reported that overexpression of the AlaAT gene could increase not only phenotypic performances but also NUE of plants even though the alanine aminotransferase enzyme is not a key enzyme in nitrogen metabolism. NUE can be used for minimizing nutrient losses and the negative impact on the surrounding environment, as well as reducing costs associated with excessive fertilizer inputs (Galloway et al 2014).…”
Section: Efficacy Of Nitrogen Use On the T2 Generation Of Homozygous ...supporting
confidence: 88%
“…Meanwhile, the M50 line revealed the highest shoot biomass and grain contents at a nitrogen fertilizer dose of 120 kg ha-1 (N3) (Figure 4). These results were in accordance with Sisharmini et al (2019) reported an increase in grain yield and tiller numbers was observed in transgenic events at 90 kg ha -1 N. 2007) and (Shrawat et al 2008) reported that overexpression of the AlaAT gene could increase not only phenotypic performances but also NUE of plants even though the alanine aminotransferase enzyme is not a key enzyme in nitrogen metabolism. NUE can be used for minimizing nutrient losses and the negative impact on the surrounding environment, as well as reducing costs associated with excessive fertilizer inputs (Galloway et al 2014).…”
Section: Efficacy Of Nitrogen Use On the T2 Generation Of Homozygous ...supporting
confidence: 88%
“…In addition, neither root-specific nor constitutive expression of HvALAAT1 using an ubiquitin promoter succeeded to increase plant biomass in Sorghum bicolor, and thus suggesting that ALAAT activity was not rate-limiting for NUE in Sorghum bicolor. Recent results have confirmed a link between a higher ALAAT activity in roots and improved N-related phenotypes since the expression of ALAAT2 from Cucumis sativus, ALAAT1 and ALAAT2 from Mus musculus, and ALAAT from Pyrococcus furiosus in either Arabidopsis or Oryza sativa successfully increased plant growth in high or low N conditions (McAllister and Good, 2015;Sisharmini et al, 2019). How ALAAT activity leads to improved agronomical performance of plants has not been clearly elucidated (McAllister et al, 2012).…”
Section: Alanine:2-oxoglutarate Aminotransferasementioning
confidence: 98%
“…Ectopic introduction of barley HvAlaAT in various N-supplied transgenic crops significantly increased the biomass and grain yield, indicating improved N use efficiency [ 76 , 77 , 78 ]. Root-specific expression of a cucumber AlaAT resulted in high N use efficiency in transgenic rice [ 79 ]. Unlike herbaceous plants, forest trees have a long lifespan and a perennial woody growth habit with sustained N nutrition by seasonal and internal cycling; therefore, investigating N’s molecular factor and regulatory mechanisms has excellent environmental significance in Populus .…”
Section: Discussionmentioning
confidence: 99%